Multifunctional bionic hydrogel for promoting intervertebral disc repair and preparation method thereof
Viscoelastic ion hydrogel (VIG) was prepared by introducing magnesium ions into PVA hydrogel and performing freeze-thaw cycles, which solved the problems of dynamicity and degradation cycle of PVA hydrogel network, and achieved efficient disc repair effect.
Patent Information
- Application Number
- CN202411401860.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-02-11
AI Technical Summary
The non-dynamic covalent polymer network and long degradation cycles of pure polyvinyl alcohol hydrogels (PVA hydrogels) seriously affect their clinical application and therapeutic effects, especially in the repair of intervertebral discs.
By introducing magnesium ions into PVA hydrogels, a viscoelastic ion hydrogel (VIG) was prepared using the Hofmeister effect of magnesium ions. This hydrogel was freeze-thawed during preparation to form a stable polymer network .
This multifunctional bionic hydrogel has the characteristics of high injection properties, frequency-dependent viscoelasticity, appropriate degradation rate, imitation of bioswelling behavior and biocompatibility, which significantly improves its therapeutic effect in intervertebral disc repair.
Smart Images

Figure CN119405902A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of bionic hydrogels, and in particular relates to a multifunctional bionic hydrogel for promoting intervertebral disc repair and a preparation method thereof. Background Art
[0002] Intervertebral disc degeneration is a multifactorial chronic disease characterized by the destruction of the inflammatory response and mechanical balance inside the intervertebral disc, which eventually causes further lesions (such as lumbar disc herniation, lumbar spinal stenosis and lumbar instability), resulting in persistent low back pain. Therefore, IVDD seriously affects the quality of life of patients and brings a huge economic burden to society.
[0003] Polyvinyl alcohol hydrogel is a small molecule polymer hydrogel with uniform structure. Due to its excellent biocompatibility and reliable mechanical properties, PVA hydrogel has been widely used in the treatment of skin defects. With the rapid development of biomaterials engineering, PVA hydrogel has gained more and more favor in different therapeutic fields and has become a material with broad application prospects. The biphasic properties exhibited by PVA hydrogel accurately reflect the biomechanical properties of the human intervertebral disc nucleus pulposus. However, the non-dynamic covalent polymer network and long degradation cycle of pure PVA hydrogel seriously affect its clinical application and therapeutic effect. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a multifunctional bionic hydrogel for promoting intervertebral disc repair and a preparation method thereof, which can overcome the above problems or at least partially solve the above problems.
[0005] The present invention is achieved by providing a multifunctional bionic hydrogel for promoting intervertebral disc repair and a preparation method thereof, comprising a hydrogel, wherein the hydrogel is a product obtained by processing a VIG solution prepared by a solution prepared by PVA and deionized water.
[0006] Preferably, the method comprises the following steps:
[0007] S1. Add PVA to deionized water to prepare 6%, 8% and 10% concentrations for later use;
[0008] S2. Place the prepared solution in a 95°C water bath and stir with a stirrer for 1 hour. Add 1.5% magnesium chloride and continue stirring at 95°C for 30 minutes to obtain a VIG solution.
[0009] S3, place it in a 95°C water bath for 15 minutes, and after the bubbles in the solution disappear, pour the PVA solution into the prepared mold;
[0010] S4. After the mixture has cooled to room temperature, it is placed in a -20°C refrigerator;
[0011] S5. Take it out of the refrigerator after 12 hours and place it at room temperature for 2 hours;
[0012] S6: One freeze-thaw cycle is 12 hours in a -20°C refrigerator and 2 hours at room temperature.
[0013] S7. The 6% VIG solution forms a gel after three freeze-thaw cycles, the 8% VIG solution forms a gel after two freeze-thaw cycles, and the 10% VIG solution forms a gel after one freeze-thaw cycle. The preparation is now complete.
[0014] S8, performing sample characterization testing;
[0015] S9, perform biocompatibility testing;
[0016] S10. Conduct animal-related experiments;
[0017] S11. Obtain results and determine the efficacy of the hydrogel.
[0018] Preferably, the sample characterization test includes scanning electron microscopy test, Fourier transform infrared spectroscopy test, hydrogel rheology test, hydrogel mechanical mechanics test, hydrogel degradation and swelling test and magnesium ion release concentration test.
[0019] Preferably, the biocompatibility test includes cytotoxicity test, live-dead staining, intervertebral disc mechanical test and immunofluorescence staining.
[0020] Preferably, the animal-related experiments include construction of animal puncture models, dehydration and embedding of animal tissue specimens, sectioning, hematoxylin-eosin staining, safranin-O-fast green staining, and immunohistochemical staining.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention prepares a viscoelastic ion hydrogel by utilizing the Hofmeister effect of magnesium ions on polyvinyl alcohol hydrogel. The viscoelastic ion hydrogel has the characteristics of high injectability, frequency-dependent viscoelasticity, suitable degradation rate, biomimetic swelling behavior and biocompatibility, and solves the problem that the non-dynamic covalent polymer network and long degradation cycle of pure PVA hydrogel seriously affect its clinical application and therapeutic effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a flow chart of the preparation of the hydrogel of the present invention.
[0024] Figure 2 The embodiments of the present invention provide the Fourier transform infrared spectrum results of each group of materials.
[0025] Figure 3The embodiments of the present invention provide rheological test results of each group of hydrogels.
[0026] Figure 4 The embodiments of the present invention provide the test results of shear viscosity of each group of hydrogels.
[0027] Figure 5 The embodiments of the present invention provide various groups of hydrogel injection diagrams.
[0028] Figure 6 The present invention provides a test diagram of the force value required for pushing injection from a syringe.
[0029] Figure 7 This is a test diagram of the self-healing ability of each group of hydrogels provided by the embodiments of the present invention.
[0030] Figure 8 This is a stress curve diagram after 200 compression cycles provided by an embodiment of the present invention.
[0031] Fig. 9 It is a degradation curve diagram of each group of hydrogels provided by the embodiments of the present invention.
[0032] Fig.10 The mass swelling curves of each group of hydrogels provided in the embodiments of the present invention.
[0033] Fig.11 The embodiments of the present invention provide scanning electron microscope images of each group of hydrogels.
[0034] Fig.12 The embodiment of the present invention provides element mapping images of each group of hydrogels.
[0035] Fig.13 The magnesium ion release curves of each group of hydrogels provided in the embodiments of the present invention are shown.
[0036] Fig.14 This is a diagram of the cell viability test results after co-culturing each group of hydrogel extracts with cells provided in an embodiment of the present invention.
[0037] Fig.15 The embodiments of the present invention provide live and dead cell staining images and quantitative results after co-culturing of each group of hydrogels and cells.
[0038] Fig.16 The present invention provides other tissue pathological staining images of each group of rats.
[0039] Fig.17 This is a graph showing the results of Collagen II and Acan fluorescence staining of NP cells provided in an embodiment of the present invention.
[0040] Fig.18 This is a graph showing the results of MMP13 fluorescence staining of NP cells provided by an embodiment of the present invention.
[0041] Fig.19 It is a schematic diagram of constructing an intervertebral disc degeneration model of SD rats provided in an embodiment of the present invention.
[0042] Fig. 20 The embodiments of the present invention provide X-ray and MRI images of SD rats on the 3rd and 7th days after puncture treatment.
[0043] Fig.21 The embodiments of the present invention provide HE and safranin / fast green staining images of the caudal intervertebral disc tissue of SD rats.
[0044] Fig. 22 The embodiment of the present invention provides an immunohistochemical staining image of the SD rat coccygeal intervertebral disc tissue.
[0045] Fig.23 The present invention provides a schematic diagram of an in vitro biomechanical test of the SD rat coccygeal intervertebral disc.
[0046] Fig.24 This is a test result diagram of the compression stiffness, tensile stiffness, energy dissipation and mobility of the coccygeal intervertebral disc of SD rats provided by an embodiment of the present invention.
[0047] Fig.25 This is a diagram showing stress relaxation results of the coccygeal intervertebral disc of SD rats provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0048] In order to further understand the content, features and effects of the present invention, the following embodiments are given as examples and described in detail with reference to the accompanying drawings.
[0049] The structure of the present invention is described in detail below in conjunction with the accompanying drawings.
[0050] like Figures 1 to 25As shown, a multifunctional bionic hydrogel for promoting intervertebral disc repair and a preparation method thereof provided in an embodiment of the present invention comprises a hydrogel, wherein the hydrogel is a product obtained by processing a VIG solution prepared by a solution prepared by PVA and deionized water. The method comprises the following steps: S1, adding PVA to deionized water, respectively preparing 6%, 8%, and 10% concentrations for standby use; S2, placing the prepared solution in a 95°C water bath, and placing a stirrer to stir for 1 hour. Add 1.5% magnesium chloride and continue stirring at 95°C for 30 minutes to obtain a VIG solution; S3, let it stand in a 95°C water bath for 15 minutes, and after the bubbles in the solution disappear, pour the PVA solution into the prepared mold; S4, after standing to room temperature, put it in a -20°C refrigerator; S5, take it out of the refrigerator after 12 hours, and let it stand at room temperature for 2 hours; S6, putting it in a -20°C refrigerator for 12 hours and leaving it at room temperature for 2 hours is a freeze-thaw cycle; S7, the 6% VIG solution becomes gel after 3 freeze-thaw cycles, the 8% VIG solution becomes gel after 2 freeze-thaw cycles, and the 10% VIG solution becomes gel after 1 freeze-thaw cycle, and the preparation is now complete.
[0051] Sample characterization tests include scanning electron microscopy testing, Fourier transform infrared spectroscopy testing, hydrogel rheology testing, hydrogel mechanical testing, hydrogel degradation and swelling testing, and magnesium ion release concentration testing.
[0052] Biocompatibility testing included cytotoxicity testing, live-dead staining, disc mechanical testing, and immunofluorescence staining.
[0053] Animal-related experiments include animal puncture model construction, animal tissue specimen dehydration and embedding and sectioning, hematoxylin-eosin staining, safranin-O-fast green staining, and immunohistochemical staining
[0054] Testing: Synthesis of PVA hydrogel
[0055] PVA was added to deionized water to prepare 6%, 8%, and 10% concentrations for later use. The prepared solution was placed in a 95°C water bath and stirred with a stirrer for 1 hour. Observe whether the solid in the beaker is completely dissolved, let it stand in a 95°C water bath for 15 minutes, and after the bubbles in the solution disappear, pour the PVA solution into the prepared mold. After standing to room temperature, put it in a -20°C refrigerator. Take it out of the refrigerator after 12 hours and place it at room temperature for 2 hours. This 12 hours in a -20°C refrigerator and 2 hours at room temperature is a freeze-thaw cycle. The 6% PVA solution gelled after 3 freeze-thaw cycles, the 8% PVA solution gelled after 2 freeze-thaw cycles, and the 10% PVA solution gelled after 1 freeze-thaw cycle. At this point, the PVA hydrogel was successfully prepared.
[0056] Synthesis of VIG hydrogel
[0057] Similarly, PVA and deionized water were used to prepare 6%, 8%, and 10% PVA solutions. After stirring in a 95°C water bath for 1 hour, 1.5% magnesium chloride was added and stirring was continued at 95°C for 30 minutes to obtain a VIG solution. It was kept still in a 95°C water bath for 15 minutes. After observing that the bubbles in the solution disappeared, the solution was poured into a predetermined container and the temperature dropped to room temperature. The 6% VIG solution gelled after 3 freeze-thaw cycles, the 8% VIG solution gelled after 2 freeze-thaw cycles, and the 10% VIG solution gelled after 1 freeze-thaw cycle. At this point, the VIG hydrogel was successfully prepared.
[0058] Sample characterization test:
[0059] Scanning electron microscope test
[0060] Place the prepared PVA hydrogel and PMG in a -80℃ refrigerator for 1 hour. After the hydrogel is completely frozen, place it in a freeze dryer for drying. After freeze drying for 3 days, check the drying of the sample and take it out after it is completely dry. Cut the sample into a suitable size and shape and fix it on the sample stage. Place the sample stage in the sample chamber of the SUPRA55 field emission scanning electron microscope. After closing the sample chamber, turn on the vacuum pump to evacuate the air in the sample chamber to ensure that the vacuum environment is maintained in the chamber. Open the Zeiss scanning electron microscope software, connect and adjust the scanning electron microscope equipment. Calibrate the microscope before starting the scan, and calibrate and adjust the scanning speed and scanning mode. Use the software to set the parameters such as the magnification and acceleration voltage of the scanning electron microscope, and adjust the parameters according to the actual situation. Adjust the focal length in the electron microscope and focus the sample so that it can be displayed clearly and accurately in the software. Start scanning, shooting and analyzing the sample.
[0061] Fourier Transform Infrared Spectroscopy Test
[0062] Fourier infrared spectroscopy is a method that uses Fourier transform of interfering infrared light to qualitatively and quantitatively analyze samples. It can observe the differences in compounds contained in small molecule monomer polymers or differences in compound structures. Therefore, this study used this principle to characterize PVA and PMG respectively. The spectral wavenumber range of the test is 4000-500cm-1, the resolution of infrared analysis is 4cm-1, and the tests are all carried out at room temperature 25°C. The samples were placed in a dry environment and the ATR accessory was installed in the optical path of the spectrometer. First, the air was scanned as the background, and then the PVA hydrogel and PMG samples were attached to the test surface of the ATR accessory, and then the infrared spectrum of the samples was received, and a total of 32 scans were performed. The transmittance between different samples was analyzed, and the peak differences between different samples were plotted and judged.
[0063] Hydrogel rheology testing
[0064] The hydrogel was prepared into a disc with a thickness of about 1 mm, and the rheological properties of the material were tested using a Discovery hybrid rheometer equipped with a temperature control unit. In the tests in oscillation mode and flow mode, the mold of the test sample adopted a flat plate to flat plate configuration, the diameter of the flat plate was 20 mm, and the gap between the upper and lower plates was 1 mm. In the rheological property test of the oscillation mode, the test conditions of 37°C, 1% strain, and oscillation frequency of 0.1Hz to 10Hz were used to determine the storage modulus (G'), loss modulus (G") and loss factor (tanδ=G" / G') of the viscoelastic hydrogel. In the oscillation test of the self-healing property, the test parameters were set to temperature: 37°C, oscillation frequency: 1Hz, strain rate: 1% for 60 seconds and 1500% for 60 seconds for a cycle. The self-healing properties of different hydrogel materials can be evaluated by plotting the measured data. At the same time, in order to obtain the transient response characteristics of the hydrogel material, a flow test was carried out on it. The test conditions were 25°C, the shear rate ranged from 0.01 / s to 100 / s, and the acquisition frequency was 1 time per second, so as to determine its steady-state flow curve.
[0065] Mechanical testing of hydrogels
[0066] In the compression cycle test experiment, PVA hydrogel and PMG were prepared into cylinders with a height of about 1 cm, and the diameter and height of each material were measured and recorded. The columnar hydrogel material was placed vertically on the stage of the universal mechanical tester, the test force value was reset to zero and the compression mold was lowered to just contact the upper surface of the columnar hydrogel. The parameters were set to the cycle mode, compressed to 30% of the height of the columnar hydrogel, the compression speed was 10 mm / min, and the number of compressions was 200 times to measure the change in force value.
[0067] In the injection force test experiment, PMG is prepared into a 20ml syringe. After the gel is completely formed, the syringe is equipped with a 25G injection needle. The syringe is fixed vertically on the test fixture so that its coronal and sagittal planes are in the same plane as the mechanical test sensor. The test force value is reset to zero and the compression mold is lowered until it just contacts the syringe push rod. The parameters are set to compression mode and the compression speed is 10mm / minute to measure the change in force value.
[0068] Degradation and swelling properties of hydrogels
[0069] In this study, the gravimetric method was used to determine the mass degradation rate in order to evaluate the degradation characteristics of PMG. The prepared hydrogel samples were dried to obtain their initial dry weight (W0). Subsequently, 10 ml of deionized water was added to each gram of material in these completely dried samples and the samples were sealed and placed in a constant temperature oven at 37°C to simulate the physiological environment in the human body. The deionized water used to soak the materials was replaced every day, and the samples were taken out of the water and re-dried at different time points to determine their new dry weight (W1). The formula for calculating the mass degradation rate is DR m =[(W0-W1) / W0]*100%.
[0070] The swelling properties of PMG were evaluated using the classical gravimetric method and the mass swelling ratio (SR) of the viscoelastic hydrogel was calculated. m First, the hydrogel sample was dried and weighed to obtain its initial dry weight (W d The dried samples were then immersed in 10 ml / g deionized water and placed in a 37°C constant temperature oven to simulate the physiological environment. After a specific time interval, the swollen hydrogel samples were taken out of the water and weighed (W s ). The mass swelling ratio is defined as SR m =[(W s -W d ) / W d ]*100%.
[0071] Magnesium ion release concentration determination
[0072] The prepared 6%, 8% and 10% PMG materials were weighed and placed in 50ml centrifuge tubes, and 1ml / 0.1g of deionized water was added respectively, and then placed in a 37°C constant temperature oven. Referring to the test weight of the PMG material, the solution in the centrifuge tube was replaced every day, and the solutions on the 1st, 3rd, 5th and 7th days were collected into clean centrifuge tubes, and the centrifuge tube caps were sealed with sealing film. The inductively coupled plasma emission spectrometer was calibrated with ultrapure water and magnesium ion standard solution, and its parameters were set as follows: plasma flow rate 16.0L / min, RF power 1300W, sample flow rate 1.5L / min, and injection time 30 seconds, so as to perform qualitative and quantitative analysis of magnesium ions in the collected liquid.
[0073] Biocompatibility testing:
[0074] Cytotoxicity assay (CCK8)
[0075] Nucleus pulposus cells were inoculated on different samples in a 24-well plate and grouped into Ctrl, 6% VIG, 8% VIG, and 10% VIG groups. The extracts of the corresponding materials were added after the cells adhered to the wall. After culturing in a cell culture incubator for 1, 3, and 5 days, the CCK-8 solution was replaced for incubation, and the OD value at a wavelength of 450 nm was measured by a microplate reader to determine the cytotoxicity.
[0076] Live dead staining
[0077] Nucleus pulposus cells were seeded on different samples of 24-well plates and grouped into Ctrl, 6% VIG, 8% VIG, and 10% VIG groups. After the cells adhered to the wall, the corresponding hydrogel materials were added. After 1 day of culture, the original culture medium was discarded: 5 μL of Calcein-AM solution (2mM) and 15 μL of PI solution (1.5mM) were added to 5mL of 1× reaction buffer, mixed thoroughly, and added to each well, and incubated at 37°C for 15 minutes. Under a fluorescence microscope, a 490±10nm excitation filter was used to simultaneously detect live cells (yellow-green fluorescence) and dead cells (red fluorescence).
[0078] Intervertebral disc mechanical testing
[0079] After completely separating the intervertebral discs and their upper and lower vertebral bodies that had undergone surgery and treatment in rats, their long and short diameters were measured. The upper and lower vertebral bodies were fixed on a universal mechanical tester so that they were kept in the same straight line with the coronal-sagittal plane of the test fixture. In the tension-compression cycle test, the cycle mode was set with parameters of 0.5N tension, 1.5N compression, and a cycle frequency of 0.5Hz. A total of 25 cycles were performed to measure the force changes of the intervertebral disc in the tension-compression cycle. In the stress relaxation test, the experiment was in compression mode with parameters of 1.5N compression and held for 600 seconds, and the force changes during the holding process were measured.
[0080] Immunofluorescence staining
[0081] NP cells were cultured on coverslips. Cells in different groups were co-cultured with IL-1β and PMG for 24 hours. Cells were fixed with 4% paraformaldehyde for 15 minutes and then treated with QuickBlock immunostaining blocking solution for 15 minutes. After rinsing three times with PBS, primary antibodies were added and incubated overnight. After rinsing three times with PBS, fluorescent secondary antibodies were added and incubated for one hour. Finally, the plates were sealed with fluorescent anti-quenching sealing solution containing DAPI. Fluorescent staining results were observed and imaged using a fluorescence microscope.
[0082] Animal related experiments:
[0083] Animal puncture model construction
[0084] Before surgery, animals were fasted for 12 h and dehydrated for 4 h. Male Sprague-Dawley rats weighing 300 g were anesthetized with 2% (w / V) pentobarbital solution at a dose of 100 mg / kg. A 21-gauge needle was used to puncture the sixth intervertebral disc of the caudal vertebra to a depth of three-quarters of the diameter of the tail. The needle was rotated for 12 s and remained in place for 18 s. Three days later, PMG hydrogel was injected through the original injection site, and the NP tissue content was calculated separately when PMG was injected.
[0085] Animal experiment group
[0086] Grouping quantity Healthy Group 10 Punctured Group 10 6%VIG group 10 8%VIG group 10 10% VIG group 10
[0087] Dehydration and embedding of animal tissue specimens
[0088] (1) After the fixed and decalcified animal tissue is trimmed into a small rectangular block that can be placed in an embedding box, the following treatments are performed: (2) 75% ethanol for 60 minutes; (3) 80% ethanol for 60 minutes; (4) 90% ethanol for 60 minutes; (5) 95% ethanol for 60 minutes; (6) anhydrous ethanol for 60 minutes × 2; (7) xylene for 45 minutes × 2; (8) immersion in 65℃ paraffin for 165 minutes and embedding; (9) cooling the paraffin specimen, fixing the wax block specimen on a tissue slicer with the sagittal plane facing forward, adjusting it to a suitable position, trimming it to a complete section including the upper and lower end plates and the middle nucleus pulposus tissue at a thickness of 10 microns, and then slicing it at a fixed thickness of 4 microns. (10) The obtained tissue slices are placed in room temperature double distilled water for preliminary expansion; (11) Secondary expansion is performed in a 45℃ slide washer; (12) Place it flat on a 60℃ slide oven to dry for 120 minutes for subsequent histological staining.
[0089] Hematoxylin-eosin staining (H&E staining)
[0090] (1) After paraffin sections were dewaxed with xylene (10 min × 3 times), they were sequentially treated with 100%, 100%, 95%, 90%, and 85% ethanol to water, each for 10 min; (2) Rinse with distilled water for 3 min, stain with hematoxylin solution for 1 min, and soak in tap water for 10 min; (3) 2% acetic acid for 1 min, and soak in tap water for 5 min; (4) Ammonia for 1 min (pulled 10 times), and soak in tap water for 5 min; (5) 95% ethanol for 5 s; (6) Eosin staining for 5 min; (7) Gradient alcohol dehydration: 95% ethanol for 2 min × 2 times; (8) Conventional dehydration, transparentization, and sealing, and observation of morphological changes of the skull under a light microscope.
[0091] Safranin-O / Fastgreen staining
[0092] The principle of Safranin-O-Fast Green staining is based on the fact that cartilage appears red when it binds to the basic dye Safranin O, while bone structure appears blue when it binds to the acidic dye Fast Green. By forming a clear contrast with the red cartilage, cartilage tissue and bone tissue can be effectively distinguished. This method can be used to observe the upper and lower end plates and vertebral structures.
[0093] (1) Melt the wax in a 60°C oven for 60 min; (2) Dewax in xylene in a fume hood for 30 min; (3) Gradient rehydration, anhydrous ethanol for 3 min × 2; (4) 95% ethanol for 3 min × 2; (5) 90% ethanol for 3 min; (6) 80% ethanol for 3 min; (7) 70% ethanol for 3 min; (8) Double distilled water for 5 min; (9) Hematoxylin staining for 5 min, double distilled water for 5 min × 3; (10) Differentiation with 1% hydrochloric acid and ethanol for 1 mi n, double distilled water for 5 min × 3; (11) 10% ammonia water for 1 min, double distilled water for 3 min × 2; (12) fast green for 6 min, double distilled water for 5 min × 3; (13) 2% acetic acid for differentiation for 1 min, double distilled water for 5 min × 3; (14) safranin for 2 min 30 s, during which time observation was made under a light microscope to avoid excessive staining, double distilled water for 5 min; (15) gradient dehydration from 90% ethanol, xylene for 3 min × 2; (16) sealing with neutral resin in a fume hood.
[0094] Immunohistochemical staining
[0095] Immunohistochemical staining combines the corresponding antibodies with the corresponding antigens in the tissue, and color changes occur under the action of DAB color developing solution.
[0096] (1) Melt the wax in a 60°C oven for 60 min; (2) Dewax in xylene in a fume hood for 30 min; (3) Gradient rehydration, anhydrous ethanol for 3 min × 2; (4) 95% ethanol for 3 min × 2; (5) 90% ethanol for 3 min; (6) 80% ethanol for 3 min; (7) 70% ethanol for 3 min; (8) Double distilled water for 5 min; (9) Antigen retrieval, methanol solution (containing 3% hydrogen peroxide solution) for 30 min; (10) PBS rinse for 3 min × 3; (11) Drain the slides slightly. Slides, avoid excessive water adhesion, use a histochemical pen to circle the specimen area, avoid repeated circling (which may lead to sealing failure); (12) 50μl hyaluronidase in the specimen area, incubate in a 37℃ constant temperature oven for 70min; (13) PBS immersion for 3min×3; (14) 50μl protease is added to the specimen area and incubated at room temperature for 30min; (15) PBS immersion for 3min×3; (16) Immunocomplex, 50μl animal serum is added to the specimen area and blocked for 10min at room temperature away from light; (17) Discard the surface serum, dilute the antibody at a ratio of 1:100, add 50 μl of primary antibody to each specimen area, and place in a 4°C refrigerator for overnight incubation; (18) Recover the primary antibody and rinse with PBS for 3 min×3; (19) Add secondary antibody to the specimen area and incubate at room temperature in the dark for 30 min; (20) Rinse with PBS for 3 min×3; (21) Color development, drain the slide slightly, add 50 μl of DAB color development solution to the specimen area for color development, prepare a large amount of double distilled water, and observe the antibody color development degree under a light microscope to avoid background If the color is too dark, a false positive result will occur, and the color development reaction should be terminated in time; (22) Rinse with PBS for 3 min × 3; (23) Counterstain with hematoxylin for 2 min, and gently rinse with double distilled water for 3 min × 3; (24) 2% acetic acid for 1 min, and gently rinse with double distilled water for 3 min × 2; (25) 10% ammonia water for 1 min, and gently rinse with double distilled water for 3 min × 2; (26) Dehydrate with gradient from 90% ethanol, and xylene for 3 min × 2; (27) Seal the slides with neutral resin in a fume hood for 2 h, and store them in a slice box after air drying.
[0097] result
[0098] 1. Characterization and detection
[0099] Fourier transform infrared spectroscopy (FTIR) Figure 2 ) showed that in pure PVA hydrogels with solid contents of 6, 8 and 10 wt.%, the characteristic stretching band of OH was between 3263.2 and 3299 cm-1. After adding Mg2+, the OH stretching band of VIG between 3206.4 and 3220.6 cm-1 did not change much. Figure 3As shown, the G′ values of the three VIGs are higher than G″. With the increase of frequency, their G′ increases from 7.42, 27.46 and 77.22Pa to 16.32, 69.70 and 237.39Pa, indicating that they are viscoelastic solids with frequency-dependent stiffness properties, which is similar to the shock absorption properties of natural NP tissues. In addition, it is worth mentioning that the G″ of all VIGs shows a stronger frequency dependence. When the frequency increases from 1Hz to 5Hz, G″ increases significantly from 1.66, 3.93 and 13.13Pa to 8.64, 37.66 and 163.40Pa, which corresponds to normal physical activities from normal walking to running. The shear viscosity analysis of the three VIGs shows that with the increase of shear rate from 0.1 to 100s-1, the viscosity gradually decreases from 0.32, 36.62 and 6661.40Pa·s to 0.23, 1.13 and 21.28Pa·s( Figure 4 ). VIG exhibits unique shear-thinning properties during injection ( Figure 5 The study found that the injection forces of the three types of VIG through a 25G injection needle were 41, 75, and 157 N, respectively ( Figure 6 ). The rheological properties of the hydrogels were tested for viscoelasticity and structural recovery after applying high shear strain. Figure 7 The results show that under high shear strain, the G″ value of VIG exceeds G′. When returning to the original low strain, the G″ of VIG instantly recovers to the initial value, while the G′ of VIG recovers to 83.5%, 89.6% and 86% of the initial value, respectively. After injection from a syringe, VIGs can withstand cyclic loads similar to those of pure PVA hydrogels, and the stress-strain correlation remains almost unchanged after hundreds of loading / unloading cycles ( Figure 8 ).
[0100] According to the degradation characteristics of the hydrogels, the mass loss rates of LS-VIG, VIG, and HS-VIG were 96%, 94%, and 91%, respectively, after immersion in deionized water for 14 days. Fig. 9 ). In contrast, pure PVA hydrogels showed a slow degradation rate both in vivo and in vitro. The swelling behavior of the hydrogels was studied. According to the swelling test results, the water absorption rates of VIG and HS-VIG were higher than those of LS-VIG ( Fig.10 To further understand the microstructure of the hydrogel, scanning electron microscopy was used to study the morphology of the polymer network by observing the cross-section of the hydrogel ( Fig.11 ). PVA hydrogel has a clear network structure composed of polymer chains, while LS-VIG has a dense block structure with few pores formed by frozen water during the drying process. In addition, the EDS spectrum of VIG shows that the hydrated Mg2+ is evenly distributed ( Fig.12), indicating its strong hydration properties. In this study, the release kinetics of Mg2+ from VIG were evaluated by soaking the samples in deionized water for up to 7 days to assess its impact on bioactivity. The hydrogel showed effective Mg2+ release on the first day with minimal degradation ( Fig.13 ). This release behavior enables VIGs to maintain a stable concentration of Mg2+ within the IDD for a specific period of time after injection.
[0101] 2. Biocompatibility results
[0102] The biocompatibility of VIGs was tested. No significant effect on cell proliferation was observed when the extracts were co-cultured with cells for 24 hours ( Fig.14 ). When cells were directly co-cultured with VIG, a large number of live cells and a small number of dead cells were observed in the control, LS-VIG, and VIG groups. However, a higher proportion of cell death was observed in the HS-VIG group ( Fig.15 ). These results indicate that the control group, LS-VIG group, and VIG group had minimal effects on cell viability. In addition, pathological analysis of various tissues of the rats showed that VIG did not cause significant harm to the rats ( Fig.16 ).
[0103] 3. Immune regulation results
[0104] IL-1β was used to simulate NP degradation of cells. In cell fluorescence staining, the fluorescence intensity of Collagen II and Acan in the IL-1β group was approximately 30% of that in the control group. The intracellular expression levels of Collagen II and Acan in the VIG group were similar to those in the control group ( Fig.17 ). MMP13 was highly expressed in the IL-1β group, indicating extracellular matrix degradation ( Fig.18 ). The results of this study demonstrated that VIG can effectively alleviate IL-1β-induced extracellular matrix degradation.
[0105] 4. In vivo results
[0106] In in vivo experiments using a rat model ( Fig.19 ), MRI of rat coccygeal tissue showed that on the third day after treatment, the water content of NP in the puncture group decreased, while the water content of NP in the VIG group remained relatively good. On the seventh day after treatment, the NP tissue in the puncture group and LS-VIG group was almost dehydrated, with low T2 density signals. The NP in the VIG group and HS-VIG group had high T2 signals, indicating that the NP tissue contained a certain amount of water ( Fig. 20The Pfirrmann scores of the VIG group on the 3rd and 7th days were lower than those of the other groups. HE and safranin / fast green staining confirmed our MRI observations, suggesting that the degree of NP degeneration in the VIG and HS-VIG groups was less than that in the puncture group ( Fig.21 ). The NP in the VIG group was more complete, and a collagen-rich matrix was observed, while in the LS-VIG group and the puncture group, the NP tissue was severely fibrotic and the typical NP tissue structure could not be observed. Immunohistochemical staining ( Fig. 22 ) showed that compared with the puncture group, the expression of collagen II and Acan in the VIG group increased by about 50%, while the expression of MMP13 in the VIG group was half of that in the puncture group.
[0107] use Fig.23 The test setup shown measures the mechanical properties of rat tail IDDs. After 50 compression-tension cycles, the tensile stiffness of the punctured group was reduced by approximately 70% compared to healthy discs, while the compressive stiffness increased significantly ( Fig.24 ). All concentrations of VIG in the material treatment group improved the tensile and compressive properties of the intervertebral disc. However, there was no statistically significant difference in the range of motion of the intervertebral disc under isodynamic forces. The absolute value of the range of motion of the intervertebral disc in the material group was reduced compared with the puncture group. After calculating the energy density per unit volume, LS-VIG and VIG improved the energy density of the degenerated intervertebral disc and restored its energy buffering function. The stress relaxation curve of 1 / 2 stress relaxation time also showed that the viscoelasticity of the intervertebral disc in the degenerated group decreased significantly, and VIG treatment was more effective in restoring the viscoelasticity of the degenerated intervertebral disc ( Fig.25 ).
[0108] Working principle of the present invention:
[0109] When in use, PVA is added to deionized water to prepare 6%, 8%, and 10% concentrations for standby use; the prepared solution is placed in a 95°C water bath and stirred with a stirrer for 1 hour. 1.5% magnesium chloride is added and continued to stir at 95°C for 30 minutes to obtain a VIG solution; it is allowed to stand in a 95°C water bath for 15 minutes, and after the bubbles in the solution disappear, the PVA solution is poured into the prepared mold; after standing to room temperature, it is placed in a -20°C refrigerator; after 12 hours, it is taken out of the refrigerator and placed at room temperature for 2 hours; this 12 hours in a -20°C refrigerator and 2 hours at room temperature is a freeze-thaw cycle; 6% VIG solution is gelled after 3 freeze-thaw cycles, 8% VIG solution is gelled after 2 freeze-thaw cycles, and 10% VIG solution is gelled after 1 freeze-thaw cycle, and the preparation is completed; sample characterization test is performed; biocompatibility test is performed; animal-related experiments are performed; results are obtained to determine the efficacy of the hydrogel.
[0110] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0111] The above description is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this patent will not depart from the scope of the technical solution of the present invention.
Claims
1. A multifunctional bionic hydrogel for promoting intervertebral disc repair, characterized in that: The invention comprises a hydrogel, wherein the hydrogel is a product obtained by processing a VIG solution prepared by a solution prepared by PVA and deionized water.
2. A method for preparing a multifunctional bionic hydrogel for promoting intervertebral disc repair, characterized in that: The multifunctional bionic hydrogel for promoting intervertebral disc repair according to claim 1, the method comprises the following steps; S1. Add PVA to deionized water to prepare 6%, 8% and 10% concentrations for later use; S2. Place the prepared solution in a 95°C water bath, add a stirring bar and stir for 1 hour, add 1.5% magnesium chloride, and continue stirring at 95°C for 30 minutes to obtain a VIG solution; S3, place it in a 95°C water bath for 15 minutes, and after the bubbles in the solution disappear, pour the PVA solution into the prepared mold; S4. After the mixture has cooled to room temperature, it is placed in a -20°C refrigerator; S5. Take it out of the refrigerator after 12 hours and place it at room temperature for 2 hours; S6: One freeze-thaw cycle is 12 hours in a -20°C refrigerator and 2 hours at room temperature. S7, 6% VIG solution gelled after 3 freeze-thaw cycles, 8% VIG solution gelled after 2 freeze-thaw cycles, and 10% VIG solution gelled after 1 freeze-thaw cycle, and the preparation was completed; S8, performing sample characterization testing; S9, perform biocompatibility testing; S10. Conduct animal-related experiments; S11. Obtain results and determine the efficacy of the hydrogel.
3. The method for preparing a multifunctional bionic hydrogel for promoting intervertebral disc repair according to claim 2, characterized in that: Sample characterization tests include scanning electron microscopy testing, Fourier transform infrared spectroscopy testing, hydrogel rheology testing, hydrogel mechanical testing, hydrogel degradation and swelling testing, and magnesium ion release concentration testing.
4. The method for preparing a multifunctional bionic hydrogel for promoting intervertebral disc repair according to claim 2, characterized in that: Biocompatibility testing included cytotoxicity testing, live-dead staining, disc mechanical testing, and immunofluorescence staining.
5. The method for preparing a multifunctional bionic hydrogel for promoting intervertebral disc repair according to claim 2, characterized in that: Animal-related experiments included the construction of animal puncture models, dehydration and embedding of animal tissue specimens, sectioning, hematoxylin-eosin staining, safranin-O-fast green staining, and immunohistochemical staining.